The role of human metaphors on urban theories and practices. Die Rolle menschlicher Metaphern für Stadttheorien und -praktiken. - Vernoos, Omid (My University, 2018)
Die Arbeit befasst sich mit der Frage, warum die Stadt einem Vergleich durch Menschen unterliegt und wie Gelehrte, Architekten und Städteplaner daraus einen Nutzen ziehen können. Man nimmt an, dass die Verwendung von menschlichen Analogien in der Städteplanung als hilfreiches Mittel dient, um städteplanerische Theorien und Projekte zu vergleichen, zu erörtern und sich komplexe städteplanerische Abhandlungen vorzustellen. Thema ist das nicht Vorhandensein einer umfassenden Studie über anthropologische Städtebautheorien und -praktiken und der Mangel an Studien über Gleichnisse in der Literatur (Architektur/Städteplanung), die als Ziel die wissenschaftliche Stadt-Diskussion haben. Als Fallbeispiele wurden die namhaftesten Autoren von anthropologische Städtebautheorien und -praktiken, vom antiken Griechenland bis in die 1960er Jahre betrachtet. Plato, Francesco di Giorgio Martini, Patrick Geddes, Le Corbusier, Lewis Mumford, Kenzo Tange, Team 10 und Metabolists wurden ausgewählt, da sie einzigartige, umfassende, methodische und herleitbare Theorien liefern oder ihre Projekte durch wissenschaftliche Metaphern begründet sind. Es wird demonstriert, dass menschliche Analogien helfen, um das Konzept "der Stadt", in den Begriffen Design, Planung und komplexer städteplanerischer Abhandlung zu verstehen.

From the very beginning, two problems arose and became the primary concern of this research: a) The absence of a comprehensive study on anthropologic urban theories and practices, b) Insufficient study on the science of metaphor in the literature of architecture and urbanism. In order to find answers, the questions of this research were divided into three main elements: the first two being the city and the human. However, what may not be apparent as the third element is the term metaphor, which incorporates the other two. Providing an answer demands putting these elements in a meaningful order and establishing a relationship between them. In this research, the discussion of metaphor is considered as the starting point and a platform on which the other elements can be resolved. Since the discussion of anthropologic urban theories and practices is fundamentally based on metaphorical expressions, it seems necessary to address the knowledge of metaphor as a fundamental matter of this dissertation. To that purpose, theories of metaphor, the application of metaphor in architectural and urban contexts, and the features that make their use inevitable will be discussed. As case studies, the authors of the most notable anthropologic urban theories and practices, from Ancient Greece up to 1960s, have been studied and included in this dissertation. Plato, Francesco di Giorgio Martini, Patrick Geddes, Le Corbusier, Lewis Mumford, Kenzo Tange, Team 10 and the Metabolists were selected because they provided unique, comprehensive, methodical and inferable theories or projects justified by scientific metaphors. In conclusion, the main studies of this research - metaphor and anthropologic urban theories and practices - are unified. It will demonstrate that the science of metaphor plays an important role in understanding and explaining urban issues. In this context, human analogy as a metaphorical approach towards urbanism helps us deal with the concept of the city in terms of design, planning and complex urban discourse.
Keywords: Stadtplanung; Stadt; Stadtmodell; Architektur; Baugeschichte; Architekturgeschichte; Moderne; Architekturtheorie; Architekturauffassung; Städtebau; Wahrnehmung; Städtebautheorie; Metapher; Stadtbegriff; Anthropologie